In-situ synthesis of large-area PANI films via sequential solution polymerization technique for electrochromic applications. (December 2021) - Chen, Rui; Zhang, Leipeng; Zhou, Yongli; Ren, Zichen; Zhang, Yiyao; Guo, Bing; Xing, Xing; Odunmbaku, George Omololu; Li, Yao; Sun, Kuan
Highlight: Sequential Solution Polymerization (SSP) led to large-area in-situ deposition of PANI films. V2 O5 nH2 O was synthesized via a modified sol-gel method and used as an eco-friendly oxidant. PANI based electrochromic devices showed excellent electrochromic properties. Abstract: Polyaniline (PANI) is a commonly used electrochromic material due to its tunable optical properties under an applied potential. In order to fabricate large-area electrochromic devices, PANI has to be deposited uniformly in large scale. Unfortunately, the existing deposition techniques can hardly meet the requirement. In this work, sequential solution polymerization (SSP) technique is introduced for in-situ deposition of large-area PANI films. This process involves synthesis of hydrated vanadium pentoxide (HVO), formation of V2 O5 precursor film and in-situ polymerization in an aniline monomer solution. PANI films with a size of 16 × 10 cm 2 are realized using bar coating in ambient. This method is facile and efficient, compatible with roll-to-roll printing technology. Electrochromic devices based on SSP PANI films exhibit high optical contract in the vis-NIR region and good cyclability. This study demonstrates that SSP shows great potential in in-situ deposition of large-area PANI films for the development of optoelectronic modules. Graphical abstract: Image, graphical abstract